ABO blood groups: A risk factor for left atrial and left atrial appendage thrombogenic milieu in patients with non-valvular atrial fibrillation. Issue 156 (August 2017) - Fu, Yuan; Li, Kuibao; Yang, Xinchun
Abstract: Background: Previous studies have identified ABO blood groups as predictors of thromboembolic diseases. In patients with atrial fibrillation (AF), however, potential association between ABO blood groups and the risk of left atrial (LA) and/or left atrial appendage (LAA) thrombogenic milieu (TM) has not been established. Methods: This is a retrospective case-control study that included 125 consecutive patients with non-valvular atrial fibrillation (NVAF) plus TM, as evidenced by transesophageal echocardiography (TEE) during a period from1 January 2010 to 31 December 2016. The controls were selected randomly from 1072 NVAF without TM at a 1:2 ratio. Potential association between ABO blood groups and TM was analyzed using multivariate logistic regression analysis. Results: The risk of TM was higher in patients with blood group A (33.6% vs. 20.2% in non-A blood groups, P = 0.005). After adjusting for age, sex, oral anticoagulant use, AF type and duration, and relevant functional measures (e.g., NT-pro BNP level, left atrium diameter, and left ventricular ejection fraction), blood group A remained associated with an increased risk of TM (OR = 2.99, 95% CI 1.4–6.388, P = 0.005). Conclusion: Blood group A is an independent risk factor for TM in NVAF patients. Highlights: ABO blood groups are known to be associated with thromboembolic diseases. We show an association of blood group A with thrombogenic milieu in NVAF patients. After adjusting relevant factors, blood group A remained a significant risk.